Species distribution models of Türkiye’s endemic genus: Seminemacheilus Banarescu & Nalbant, 1995 (Cypriniformes: Nemacheilidae) - Sungur Sevil (Oceanological and Hydrobiological Studies)
Climate change is having a major impact on species distribution and habitat loss, especially for species with restricted ranges. The genus Seminemacheilus is endemic to Türkiye and includes six species. This study investigated the current distribution of the genus Seminemacheilus and its possible distribution in 2050 and 2070 using the Wallace platform, a Maxent modeling method. Simulations of future projections indicated that bioclimatically suitable habitats of Seminemacheilus spp. will be limited in 2050 and nearly extinct in 2070. The model is primarily affected by temperature and precipitation, which are directly associated with the phenomenon of global warming. It has been established that conservation strategies must be developed to protect the species of the genus and avoid habitat deterioration.